Hopscotch Game to Support Stimulus in Children’s Gross Motor Skill using IoT - Jati, Riyan Kuncoro; Suwastika, Novian Anggis; Yasirandi, Rahmat (Universitas Muhammadiyah Malang, 2020)
Every movement that has connection to stability and coordination between each body part were accounted as the gross motor skill system. If gross motor skill development were interrupted especially for 3-5 years old, their activities would be negatively affected. Foot-based games such as jumping and stepping can be used to train a child's motor balance. One example of a famous traditional game is hopscotch. Hopscotch is a game that demand high flexibility of foot movement a coordination skills thus proved scientifically can train children gross motor skill system. Various types of hopscotch games have the potential to improve children's dynamic balance. But in traditional hopscotch games it is difficult to see how the mechanism of improving children's dynamic balance is established. The development of a child's dynamic balance cannot be constantly tracked by teachers or parents. Therefore, we design and create hopscotch with an automated system that can overcome these limitations with digital records, data stored safely, system requirements easily duplicated, and more accurate. In the Hopscotch game, there are features, namely levels 1–3, and memory test, where the memory test serves to train children's memory. The hopscotch game using Footstep based capacitive sensor and LED feedback, the improved gameplay used for training and measuring child’s gross motor skill system by their time completion and true/false footstep ratio. As the result the IoT based Hopscotch game with randomized lane are successfully mimic hopscotch gameplay with its added gameplay feature, the player subject performance has increased adaptability performance through each level the capacitive sensor-based footprint system has shown 100% accuracy, the system fully response to the footstep with average 456 milliseconds reading time per step, the system interface can fully control the gameplay level and can show players performance.